2016
DOI: 10.1021/jacs.6b04039
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Carbon Dioxide Adsorption and Morphological Changes on Cu(100) and Cu(111) at Ambient Pressures

Abstract: Ambient-pressure X-ray photoelectron spectroscopy (APXPS) and high-pressure scanning tunneling microscopy (HPSTM) were used to study the structure and chemistry of model Cu(100) and Cu(111) catalyst surfaces in the adsorption and dissociation of CO2. It was found that the (100) face is more active in dissociating CO2 than the (111) face. Atomic oxygen formed after the dissociation of CO2 poisons the surface by blocking further adsorption of CO2. This "self-poisoning" mechanism explains the need to mix CO into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
145
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 46 publications
22
145
3
Order By: Relevance
“…(C) The adsorption of CO 2 when a subsurface oxide structure is deliberately incorporated into Cu(111) but without additional H 2 O. In this work we observe that a subsurface oxide coverage of about 0.08 ML is responsible for stabilizing l-CO 2 determining the initial species formed while exposed to realistic gas pressures of CO2 and H2O (13,15).…”
Section: Significancementioning
confidence: 64%
See 2 more Smart Citations
“…(C) The adsorption of CO 2 when a subsurface oxide structure is deliberately incorporated into Cu(111) but without additional H 2 O. In this work we observe that a subsurface oxide coverage of about 0.08 ML is responsible for stabilizing l-CO 2 determining the initial species formed while exposed to realistic gas pressures of CO2 and H2O (13,15).…”
Section: Significancementioning
confidence: 64%
“…2D, experimental condition A). Such subsurface adsorbed O (denoted Cu-O sub ) has been observed often near the Cu surface, most likely resulting from oxygen impurities in the chamber (28) or partial dissociative adsorption of CO2 (13). Interestingly, even if CO2 is still in a linear configuration (similar to the gas phase), we observe experimentally that the O 1s and C 1s core-level BEs of l -CO2 shift downward by ∼4.9 eV compared with g-CO2 (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…[11,[18][19][20][21][22] The conventional electron and ion probes are ineffective owing to their favored operation conditions of very low pressures, under which catalytic surfaces may be substantially different from those at ambient pressures, especiallyf or the adsorption of low-sticking species. [11,[18][19][20][21][22] The conventional electron and ion probes are ineffective owing to their favored operation conditions of very low pressures, under which catalytic surfaces may be substantially different from those at ambient pressures, especiallyf or the adsorption of low-sticking species.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Among these parameters,t he catalyst structure and chemical state are of particular importance. [7,8,16,21,[30][31][32][33][34][35][36] However,t he presence of (100) facets is not the only factor responsible for the superior activity and selectivity of cubeshaped Cu catalysts,w ith surface roughness,s ubsurface oxygen and Cu I species or Cu/Cu I interfaces formed and/or stabilized under reaction conditions also playing av ery important role. [20][21][22][23][24][25][26][27][28][29] Previous studies [9][10][11] on Cu single crystals have shown the improved C À Cc oupling performance of (100) facets,w hich was further confirmed by the high selectivity towards ethylene observed on cube-shaped Cu catalysts.…”
mentioning
confidence: 99%